Prognostic role of multiple biomarkers in stable patients undergoing fractional flow reserve-guided coronary angioplasty. Issue 9 (September 2016) - Fracassi, Francesco; Niccoli, Giampaolo; Scalone, Giancarla; Di Gioia, Giuseppe; Conte, Micaela; Bartunek, Jozef; Sgueglia, Gregory A.; De Bruyne, Bernard; Montone, Rocco A.; Wijns, William; Crea, Filippo; Barbato, Emanuele
Abstract : Aims: Fractional flow reserve (FFR)-guided percutaneous coronary intervention (PCI), along with optimal medical therapy, improves clinical outcome by targeting ischemia-inducing stenosis. Yet, plaque progression or stent failure may cause recurring cardiac events. We assessed the potential prognostic role of different inflammatory biomarkers, known to be associated with plaque progression or stent failure, in patients undergoing FFR-guided PCI. Methods: We prospectively enrolled 169 stable angina patients with intermediate coronary stenosis at angiography undergoing FFR-guided PCI. PCI was performed if FFR was 0.80 or less, deferred if FFR was more than 0.80. Serum baseline levels of high-sensitivity C-reactive protein (hs-CRP), eosinophil cationic protein (ECP), cystatin-C (Cys-C), and thromboxane A2 (TXA2) were assessed. Rate of major adverse cardiovascular events (MACE), defined as a composite of cardiovascular death, recurrent myocardial infarction, and target vessel revascularization (TVR), was evaluated. Results: PCI was performed in 78 patients (46%) (mean age 69 ± 10 years, men 73%) and deferred in 91 patients (54%) (mean age 64 ± 11 years, men 53%). Mean clinical follow-up was 31 ± 11 months. Within the PCI group, patients with MACE ( n = 14 [18%]) had significantly higher ECP levels than those without (14.4 [9.3–19.5] vs. 4.9 [2.8–10.9] mg/l, P < 0.001), and ECP was a significant predictor of MACE (hazard ratio: 1.05, 95% confidence interval [1.01–1.09], P = 0.021). Within the deferred group, patients with MACE ( n = 8 [9%]) had significantly higher CRP levels than those without (15 [6.5–31.9] vs. 1.6 [0.9–2.9] mg/l, P < 0.001) and CRP was a significant predictor of MACE (hazard ratio: 1.04, 95% confidence interval [1.01–1.07], P = 0.015). Cys-C and TXA2 were not significantly different between the two groups. Conclusion: Assessing inflammatory biomarkers allows the identification of patients remaining at residual higher risk of MACE after FFR-guided PCI.